1999
DOI: 10.1074/jbc.274.45.32182
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Ligand Binding Specificity of the α1β1 and α2β1Integrins

Abstract: The ␣ 1 ␤ 1 and ␣ 2 ␤ 1 integrins are cell surface collagen receptors. Cells expressing the ␣ 1 ␤ 1 integrin preferentially adhere to collagen IV, whereas cells expressing the ␣ 2 ␤ 1 integrin preferentially adhere to collagen I. Recombinant ␣ 1 and ␣ 2 integrin I domains exhibit the same collagen type preferences as the intact integrins. In addition, the ␣ 2 integrin I domain binds echovirus 1; the ␣ 1 I domain does not. To identify the structural components of the I domains responsible for the varying ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 30 publications
2
58
0
Order By: Relevance
“…Again the authors suggested that these findings implied that each ligand interacted with somewhat different sites on the same integrin. Perhaps the most convincing evidence in support of this idea comes from recent reports that echo virus and collagen bind to two distinct sites on the isolated insertional domain from the integrin ␣2 subunit (26), a finding that has been confirmed by differential effects of substitutions within this domain on adhesion to each ligand (27).…”
Section: Fig 11mentioning
confidence: 78%
“…Again the authors suggested that these findings implied that each ligand interacted with somewhat different sites on the same integrin. Perhaps the most convincing evidence in support of this idea comes from recent reports that echo virus and collagen bind to two distinct sites on the isolated insertional domain from the integrin ␣2 subunit (26), a finding that has been confirmed by differential effects of substitutions within this domain on adhesion to each ligand (27).…”
Section: Fig 11mentioning
confidence: 78%
“…Binding of DMP1 to Immobilized Type I Collagen-A solidphase binding assay was used as the method of choice for characterization of interactions between collagen and noncollagenous proteins (8,23). The binding curves shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The collagen was then dissolved in 0.01 M HCl at a 1 mg/ml concentration. Collagen binding property (23) was determined by coating microtiter plates (Immulon 4, Dynex Technologies) with 5 g of type I collagen in 100 l of 0.1 M acetic acid/well overnight at 4°C. Wells were washed three times with PBS and blocked with 0.5% (w/v) bovine serum albumin in PBS at 37°C for 2 h before the addition of varying concentrations of the GST-fused recombinant DMP1 (24).…”
Section: Solid-phase Binding Assay Of Dmp1 With Monomeric Collagen-mentioning
confidence: 99%
“…In contrast, the VWF-A3 domain appears to function as an independent structural unit, and there is no evidence for modulation of its collagen binding affinity, nor does binding of A3 to collagen appear to affect the affinity of the VWF-A1 domain for platelet receptor GpIb␣. Thus, the collagen-binding site of A3 merely performs an adhesive function, whereas binding sites of I domains are more sophisticated and also play a regulatory role (31).…”
Section: Discussionmentioning
confidence: 99%